Indigenous Data Sovereignty, Circular Systems, and Solarpunk Solutions for a Sustainable Future - Alipio, Ka'ulawena; García-Colón, Javier; Boscarino, Nima; Fox, Keolu (Pacific Symposium on Biocomputing. Pacific Symposium on Biocomputing, 2025)
Recent advancements in Artificial Intelligence (AI) and data center infrastructure have brought the global cloud computing market to the forefront of conversations about sustainability and energy use. Current policy and infrastructure for data centers prioritize economic gain and resource extraction, inherently unsustainable models which generate massive amounts of energy and heat waste. Our team proposes the formation of policy around earth-friendly computation practices rooted in Indigenous models of circular systems of sustainability. By looking to alternative systems of sustainability rooted in Indigenous values of aloha 'āina, or love for the land, we find examples of traditional ecological knowledge (TEK) that can be imagined alongside Solarpunk visions for a more sustainable future. One in which technology works with the environment, reusing electronic waste (e-waste) and improving data life cycles.